Development and Validation of High Performance Liquid Chromatography Method for Analysis of Gatifloxacin and Its Impurity - G. CHANDORKAR, JAYANT; V. PANDE, VISHAL; DUBEY, SONAL; CHANDEWAR, A.V. (Asian Journal of Chemistry, 2010)
A simple isocratic reverse phase high performance liquid chromatographic method was developed for the intermediates and finished products in reaction stream during process development of gatifloxacin. The method was utilized successfully in analyzing the reaction streams, related substances in final product and for the assay in drug.